Advances in accounting education. Vol. 10 - Schwartz, Bill N.; Catanach, Anthony H. (Emerald, 2009)
Advances in Accounting Education is a referenced, academic research annual whose purpose is to help meet the needs of faculty members interested in ways to improve their classroom instruction. We publish thoughtful, well-developed articles that are readable, relevant and reliable. Articles may be either empirical or non-empirical. They emphasize pedagogy i.e. explaining how faculty members can improve their teaching methods or how accounting units can improve their curricula/programs.
Helps meet the needs of faculty members interested in ways to improve their classroom instruction. This title includes articles that emphasize pedagogy that is explaining how faculty members can improve their teaching methods or how accounting units can improve their curricula/programs.
Keywords: Accounting -- Study and teaching.; elektronické knihy; electronic books